Role of IGF1‐(CA)19 promoter microsatellite in the clinical presentation of acromegaly. (December 2014) - Sala, Elisa; Filopanti, Marcello; Ferrante, Emanuele; Barbieri, Anna Maria; Malchiodi, Elena; Verrua, Elisa; Giavoli, Claudia; Lania, Andrea G.; Arosio, Maura; Beck‐Peccoz, Paolo; Spada, Anna; Mantovani, Giovanna
Abstract Background A highly polymorphic Cytosine–Adenosine (CA) repeat sequence microsatellite has been identified in the promoter region of IGF1 gene. Several studies investigated the relationship between IGF1‐(CA)n polymorphism and IGF1 levels, with conflicting results. Aim of this study was to investigate the influence of this polymorphism on clinical and biochemical characteristics of acromegalic patients. Methods Eighty‐eight acromegalic patients and 104 normal subjects were included in the study. Blood DNA was extracted and analysed by microsatellite technique using capillary electrophoresis. Patients and controls were subdivided in 19/19 [homozygous for the (CA)19 allele], 19/X [heterozygous for the (CA)19 allele] and X/X (any other genotype). Results The genotype frequency was significantly different between patients and controls, the proportion of 19/19 being lower (28·4% vs. 50·0%) and 19/X and X/X higher in acromegalic patients than in controls (P = 0·004). There were no significant differences in age, gender, basal and nadir GH, IGF1‐SDS, tumour size, metabolic parameters, outcome and treatment among the three groups. The different frequency of genotypes in acromegalic patients vs. controls, as well as the lack of relationship between IGF1‐(CA)n polymorphism and clinical and biochemical data in acromegalic patients, was confirmed using an additional alternative genotyping considering (CA)19 and (CA)20 homozygotes and heterozygotes vs. alleles with more than 19 of 20 repeats or less. Conclusions Our results do not support the hypothesis that IGF‐(CA)n alleles may have a significant role in determining clinical, biochemical and outcome of patients with acromegaly. The possible role of IGF1 polymorphism on susceptibility to acromegaly remains to be investigated.